Managerial Use of Disciplinary Measures and Absenteeism among Frontline Health Workers: The Moderating Roles of Job Resources and Job Demands - Munyenyembe, Benson (The Journal of Behavioral Science, 2022)
Whilst managers continue to leverage the use of disciplinary measures to improve employee work attendance behavior, its effectiveness remains under probe as voluntary employee absenteeism persist. Drawing on the deterrence theory of punishment and the job demands-resources model the study investigated contingency factors that influence the effectiveness of managerial use of disciplinary measures to reduce’ absenteeism among frontline health workers in Malawi. The study used a cross-sectional survey method, that recruited 475 frontline health workers as participants. To test all the hypotheses that were proposed in the study, PLS-SEM was used. The results revealed that managerial use of disciplinary measures had a direct negative effect on absenteeism (β = -.15, p = .00). The results indicated that managerial coaching had an insignificant moderating effect in the relationship between job demands and absenteeism (β = -.02, p = .10). The results indicated, however, that emotional job demands (β = .20, p = .00) and physical job demands (β = .23, p = .00) both had significant moderating effects in the relationship between managerial use of disciplinary measures and absenteeism. These findings imply that managerial use of disciplinary measures to reduce absenteeism is more effective on employees experiencing lower emotional and physical job demands as compared to those experiencing higher emotional and physical job demands.